Women in Austrian international trade - Birgit Meyer; Klaus S. Friesenbichler; Harald Oberhofer (FIW - Research Centre International Economics, 2024)
This study is the first to examine employment effects by gender in Austrian firms and thus provides insight into the role of Austrian firms engaged in foreign trade for women's labour market opportunities and participation in firms. Using a matched employer-employee dataset based on various microdata from the Austrian Micro Data Center (AMDC) of Statistics Austria, the study looks at different indicators and possible differences between female employees in foreign trade-affiliated firms compared to exclusively domestic firms.
Keywords: F14; F16; J16; J31; 330; International Trade; Gender Pay Gap; Female labour force participation; Matched employer-employee data; Exporter